Knuckle Pads Successfully Treated with 2% Crisaborole Ointment Combined with Triamcinolone Acetonide and Neomycin Plaster: A Case Report - Liang Y; Liang J; Huang Q; Tian X; Shao L; Xia M; Liu Y (Dove Medical Press, 2023)
Yimin Liang,* Jingyao Liang,* Qiongxiao Huang, Xin Tian, Lei Shao, Manqi Xia, Yumei Liu Institute of Dermatology, Guangzhou Medical University, Department of Dermatology, Guangzhou Institute of Dermatology, Guangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Yumei Liu, Department of Dermatology, Guangzhou Institute of Dermatology, 56 HengFu Road, Guangzhou, 510095, People's Republic of China, Tel +86-13660403350, Email liuyumei1109@163.comAbstract: Knuckle pads (KPs) are benign hyperkeratotic fibrous thickening skin disorder characterized by nodules or plaques located on the extensor surface of the joints. However, there are no specific treatments for KPs so far. Here, we reported a case of KPs successfully treated with 2% crisaborole ointment combined with triamcinolone acetonide and neomycin plaster. This combined therapy might be a new therapeutic option for KPs.Keywords: knuckle pads, crisaborole, PDE-4 inhibitors, primary, emerging therapy